An Orthographic failure analysis in written German of students - Ilir Krusha (Prizren Social Science Journal, 2018)
The planned analysis follows the view that spelling is an issue that has been preoccupying German society for several centuries. Linked to this is also the spelling performance of students an often controversial topic. The focus of the newly launched school reform was on individuality and equal opportunities. Despite everything, the depth of expertise in the existing school reforms seems to diverge greatly, as well as with regard to German lessons and the related knowledge of German orthography. This work tries to get an answer to this phenomenon. The theoretical part discusses influencing factors on the acquisition of written language, the most important key data of the German history of orthography and a scientifically founded knowledge of the areas of upper and lower case as well as separation and combination.